APRESIASI SENI GALERI VIRTUAL PENCIPTAAN SENI RUPA DAN DESAIN MELALUI TEMA GRES - Handriyotopo Handriyotopo (JADECS (Journal of Art, Design, Art Education and Culture Studies))
Appreciation of a work of art, whether in two-dimensional or three-dimensional form, is currently widespread enough to carry out exhibitions in public spaces or exhibitions in the form of conventional spaces and virtual spaces. Many of these digital virtual exhibition platforms come with various applications for designing virtual spaces. Postgraduate students in the art study program, master of arts program, and doctoral program at the Indonesian Institute of the Arts are required not only to create creative works of art but also to be able to appreciate art exhibitions in virtual space. Seeing the condition of the development of digital technology and works of art in a virtual gallery, the ISI Surakarta Postgraduate School needs to create a model of the virtual gallery space so that postgraduate students and lecturers can use it. As a pilot project for applied arts in this virtual gallery, it is in the Studio 2 Fine Arts and Design course in the master's program with an interest in art creation. This design uses a virtual reality platform, Google Sketchup, and other 3D applications. The many advantages of this device are that it is light, easy to use, and can be accessed by all devices. The Gres virtual gallery uses the studio.panoee.com application to present a showroom for works of art and design so visitors can widely appreciate it.